2002
DOI: 10.1074/jbc.m201387200
|View full text |Cite
|
Sign up to set email alerts
|

Proteins from Mucuna pruriens and Enzymes fromEchis carinatus Venom

Abstract: Mucuna pruriens seeds have been widely used against snakebite in traditional medicine. The antivenin property of a water extract of seeds was assessed in vivo in mice. The serum of mice treated with extract was tested for its immunological properties. Two proteins of Echis carinatus venom with apparent molecular masses of 25 and 16 kDa were detected by Western blot analysis carried out using IgG of mice immunized with extract or its partially purified protein fractions. By enzymatic in-gel digestion and electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 35 publications
3
34
0
Order By: Relevance
“…It could be observed that the best performances were obtained at acidic condition. These results of good performance in acidic medium are supported by previous reports [6]. Figure 8 specifically revealed that the maximum efficiency of 96.41% was obtained at pH 4.…”
Section: Effect Of Time and Ph Variation On Treatment Performancesupporting
confidence: 80%
See 1 more Smart Citation
“…It could be observed that the best performances were obtained at acidic condition. These results of good performance in acidic medium are supported by previous reports [6]. Figure 8 specifically revealed that the maximum efficiency of 96.41% was obtained at pH 4.…”
Section: Effect Of Time and Ph Variation On Treatment Performancesupporting
confidence: 80%
“…Mucuna is of an annual twinning tropical plant, which contains thickening seed bean that is composed of soluble proteins (20-30%), lipids, fibers, and minerals [6]. Results obtained from the preliminary application of novel Mucuna seed coagulant (MSC) in the treatment of coal washery effluent indicated its prospects for potential utilization in the treatment of produced water (PW), which constitutes aquatic pollutant in Nigeria's Niger Delta region [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The activity may be attributed to the presence of enzymatic inhibitors, chemical inactivators, or immunomodulators present in the plant isolates [11]. Guerranti et al [12] demonstrated that the presence of proteins from seed extract of Mucuna pruiens protected mice against the toxic effects of Echis carinatus venom. It does so by an immunological mechanism based on a series of specific epitopes common to some vegetal and venom proteins.…”
mentioning
confidence: 99%
“…The mechanisms of the protective effects exerted by M. pruriens seed aqueous extract (MPE) were investigated in detail in a study involving the effects of echis carinatus venom (EV). [15] In vivo experiments on mice showed that protection against the poison is evident at 24 h (short term) and 1 month (long term) after injection of MPE. [16] MPE protects mice against the toxic effects of EV through an immune mechanism.…”
Section: Antivenom Activitymentioning
confidence: 99%
“…M. pruriens plant has many activities which need to elaborate for future cure in Ayurvedic tradition. [15] Antidiabetic Plant seed Ethanol/water (1:1) Cyclitols, oligosaccharides [21] Antioxidant Whole plant Methanol Phenols, tannins [22] Neuroprotective Plant seed, whole plant Ethanol/water (1:1) L-DOPA, amino acids, alkaloids n-propanol Isoquinolines, alkaloids [25] Antimicrobial Plant leave Methanol Tannins, alkaloids, L-DOPA [27] …”
Section: Antioxidant Activitymentioning
confidence: 99%